17 - Report of the CODESRIA/ECA Conference of Directors of Social Science Research Institutes and Policy-Makers on the Third United Nations Development Decade, the Monrovia Strategy and the Lagos Plan of Action: Addis Ababa, March 1-4 1982 - journal system, (Africa Development, 1982)
Report of the CODESRIA/ECA Conference of Directors of Social Science Research Institutes and Policy-Makers on the Third United Nations Development Decade, the Monrovia Strategy and the Lagos Plan of Action: Addis Ababa, March 1-4 1982